An in-vitro study of the sterol content and toxin production of Fusarium isolates from mycotic keratitis - Raza, S. K.; Mallet, A. I.; Howell, S. A.; Thomas, P. A. (Journal of Medical Microbiology, 1994)
Summary Isolates of Fusarium species from 18 patients with keratomycosis were examined for their C-29 and C-31 sterol content and for their capacity to synthesise mycotoxins. All isolates were resistant to azole antifungal agents in vitro and the sterol contents were indistinguishable. In-vitro toxin production was monitored by gas chromatography–mass spectrometry; 13 isolates produced nivalenol, six produced deoxynivalenol, nine gave T-2 toxin and two showed the presence of diacetoxyscirpenol at different time intervals. However, neither sterol content nor toxin production in vitro appeared to be related to the severity of infections observed in patients.